A bivariate probit analysis of child passenger's sitting behaviour and restraint use in motor vehicle. (August 2019) - Aidoo, Eric N.; Ackaah, Williams; Appiah, Simon K.; Appiah, Ernest K.; Addae, Joseph; Alhassan, Haruna
Highlights: Sitting behaviour and restraint use among child passengers were investigated. Cross-sectional observational survey data and bivariate probit model were used in this study. The rate of front sitting and restraint use among child passenger were 26% and 4.5%, respectively. The model suggests a positive relationship between front sitting behaviour and restraint use among child passengers. Abstract: Motor vehicle injuries are a leading cause of death among children worldwide, though many of these deaths are preventable. Buckling young children in age- and size-appropriate car seats, booster seats, or seat belts and also seating them in appropriate position can lead to a significant reduction of serious and fatal injuries. This study investigated sitting behaviour and restraint use among child passengers through cross-sectional observational surveys conducted in Kumasi, Ghana. A bivariate probit model was developed for simultaneous determination of the contributing factors influencing child passenger's sitting behaviour and restraint use. The results showed that 26% of the child passengers observed were occupying the front seat and the prevalence rate of restraint use was 4.5%. The developed bivariate probit model clearly highlights the existence of interrelationship between child passenger's sitting position and restraint use. The key factors simultaneously influencing child passenger's sitting position and restraint use include vehicle type, driver's gender, driver's belt use, child's age, and the presence of other child or adult passenger. Furthermore, time of day and day of week also influence child passenger sitting behaviour but not their restraint use. These findings provide insight for better understanding of child transporting practices and the contributing factors influencing their sitting behaviour and restraint use. The findings also highlight the need for policy makers to design effective countermeasures to promote rear sitting and restraint use among child passengers.